Existence of Solitary Waves and Periodic Waves to a Perturbed Generalized KdV Equation - Yan, Weifang; Liu, Zhengrong; Liang, Yong (Mathematical Modelling and Analysis, 2014)
In this paper, the existence of solitary waves and periodic waves to a perturbed generalized KdV equation is established by applying the geometric singular perturbation theory and the regular perturbation analysis for a Hamiltonian system. Moreover, upper and lower bounds of the limit wave speed are obtained. Some previous results are extended.